Integrating Digital Embroidery Techniques into Modern Textile Education for Students - Nematova Tursuntosh Alisher qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article investigates the integration of digital embroidery techniques into modern textile education for students. Combining traditional embroidery with digital tools enhances creativity, technical skills, and design efficiency. The study examines pedagogical methods for teaching digital embroidery, project-based applications, and its impact on students’ artistic, cognitive, and professional development. Research demonstrates that incorporating digital embroidery into education nurtures innovation, aesthetic awareness, and cultural preservation.